2015
DOI: 10.18869/acadpub.cmm.1.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Pneumocystis jirovecii using polymerase chain reaction in immunocompromised patients with pulmonary disorders in northeast of Iran

Abstract: Background and Purpose:Pneumocystis pneumonia, caused by Pneumocystis jirovecii, is a fatal disease threatening patients with AIDS or immunosuppression. Assessment of colonization in these patients is of great significance, since it can lead to severe pulmonary disorders. Considering the scarcity of published reports on Pneumocystis jirovecii isolates from patients in Mashhad, Iran, we aimed to evaluate pneumocystis colonization in individuals with different pulmonary disorders.Materials and Methods:We used ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Nonetheless, methenamine silver staining and immunofluorescence assay have lower sensitivity [15, 22]. Nested PCR and sequencing, compared with other staining methods, reportedly show the highest sensitivity and quality that is in agreement with the results of the present study [16, 17]. However, in a study performed on normal individuals, there was no difference between PCR and conventional methods in the diagnosis of P. jirovecii [23].…”
Section: Discussionsupporting
confidence: 86%
“…Nonetheless, methenamine silver staining and immunofluorescence assay have lower sensitivity [15, 22]. Nested PCR and sequencing, compared with other staining methods, reportedly show the highest sensitivity and quality that is in agreement with the results of the present study [16, 17]. However, in a study performed on normal individuals, there was no difference between PCR and conventional methods in the diagnosis of P. jirovecii [23].…”
Section: Discussionsupporting
confidence: 86%
“…9 In the Parian et al study in a similar region (Northeastern Iran) in 2015, a 16.66% prevalence was reported via the nested PCR method. 16 Although these studies showed a relatively similar prevalence, the studied population and molecular method can influence other results. It seems the qualitative diagnostic methods are not enough to predict the status of P. jirovecii infection because they cannot differentiate the colonization and invasion.…”
Section: Discussionmentioning
confidence: 93%
“…9 In the Parian et al study in a similar region (Northeastern Iran) in 2015, a 16.66% prevalence was reported via the nested PCR method. 16 Although these studies showed a relatively similar prevalence, the studied population and molecular method can influence other results.…”
Section: Discussionmentioning
confidence: 93%
“…In a study conducted by Aboualigalehdari et al in Ahvaz, Iran the prevalence of P. jirovecii was totally 27% including, 32.1% in tuberclosis patients, 25.3% in other chronic pulmonary disorders, and 25.3% in HIV patient ( 20 ). In another study by Parian et al the results of PCR and sequencing tests demonstrated that 10 BAL samples were colonized by P. jirovecii ( 21 ). Also, a study performed by Azoulay in 2004 in Paris showed the rate of positive samples to be 8.7% ( 22 ).…”
Section: Discussionmentioning
confidence: 98%